A 14-year-old boy with Isolated Tuberculous Orchitis - Gurubacharya, RL; Gurubacharya, SM (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The genitourinary tract is the most common extrapulmonary site affected by tuberculosis. The male genital organs are involved in more than 50% of patients. The epididymis is the commonest structure to be involved, followed by the seminal vesicles, prostate, testis, and the vas deferens. An isolated tuberculous orchitis without epididymal involvement is rare. This case report describes extra pulmonary tuberculosis with exclusively testicular presentation. The confirmatory diagnosis of which was made by FNAC of the testis. It provides a successful diagnosis, thereby preventing unnecessary orchidectomy. Key words: genitourinary tuberculosis, testis, USG, FNAC doi:10.3126/jnps.v29i1.1598 J. Nepal Paediatr. Soc. Vol.29(1) p.30-32